2002
DOI: 10.1002/mde.1093
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic news and the returns of financial companies

Abstract: This research is concerned with the response of the NASDAQ Financial 100 index to macroeconomic news. The paper employs the newly developed technique of generalized impulse response analysis to examine how macroeconomic shocks affect the performance of the financial sector. The results identify the magnitude and persistence of the response of financial companies stock returns arising from shocks to the stance of monetary policy, real output, inflation, and risk. The findings add to the literature on the determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…But when they applied Granger causality test on the set of macro variables chosen for their study, they found that the Korean stock index is not a leading indicator for the economic variables. Ewing (2002), using the technique of 'Generalised impulse response analysis' on the NASDAQ financial 100 Index, applying the shock of four economic variables (i.e. inflation, monetary policy, output, and risk), found that monetary policy have an impact on stock return for a period of two month, and unexpected economic growth has a bearing on the stock return but it could not sustain in the long run, and the inflation is negatively related with the stock return.…”
Section: Literature Reviewmentioning
confidence: 99%
“…But when they applied Granger causality test on the set of macro variables chosen for their study, they found that the Korean stock index is not a leading indicator for the economic variables. Ewing (2002), using the technique of 'Generalised impulse response analysis' on the NASDAQ financial 100 Index, applying the shock of four economic variables (i.e. inflation, monetary policy, output, and risk), found that monetary policy have an impact on stock return for a period of two month, and unexpected economic growth has a bearing on the stock return but it could not sustain in the long run, and the inflation is negatively related with the stock return.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The variables include interest rate, inflation, exchange rate, industrial production and money supply. Ewing (2002) examined the response of returns to shocks of four key economic variables, i.e. monetary policy, output, risk and inflation on the NASDAQ Financial 100 Index.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Some notable studies related to macroeconomic indicators and stock market in different countries (kwon and Shin, 1999) in South Korea, Ibrahim (1999) for Malaysia. Ewing (2002) examined the response of return between NASDAQ Financial 100 index to shocks of macroeconomic variables, i.e. output, risk, monetary policy and inflation by applying new techniques of general impulse response analysis.…”
Section: Literature Reviewmentioning
confidence: 99%